Social Prerequisites of the Emergence of Ethics in Ancient Greece - Rybakovienė, Vanzeta (Problemos, 1977)
The author attempts to show how the changes of social conditions of ancient Greeks (the establishment of slave-owning social relations and more intensive cooperation with other nations) discharge the individual from unconditional power of tribal traditional laws and provide conditions for the establishment of morality as something distinct from the community’s traditional norms of behaviour. The distinction between obligatory and generally accepted norms gives rise to ethics as a science of morals.